Crítica de la libertad sindical - Ermida Uriarte, Oscar (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Critique of trade union freedomThe article begins of the protective character of Labor Law and of the study of trade union freedom as an instrument of compensatory inequality, to analyze critically the protection of this right in the Committeeof Trade Union Freedom. Then, it develops causes of the current crisis of trade unionism and the possibility of atrade union self-reform and of an International Court of Trade Union Freedom. Finally, the article presents some strategies for overcoming the crisis of trade unionism

El artículo parte del carácter protector del derecho del trabajo y del estudio de la libertad sindical como instrumento de desigualdad compensatoria, para analizar críticamente la protección de este derecho enel Comité de Libertad Sindical. Seguidamente, se desarrollan las causas de la actual crisis del sindicalismo y la posibilidad de una autorreforma sindical y de un Tribunal Internacional de la Libertad Sindical. Finalmente, el artículo presenta algunas estrategias para superar la crisis del sindicalismo
Keywords: Relaciones colectivas; Libertad sindical; Tutela colectiva; Sindicalismo; https://purl.org/pe-repo/ocde/ford#5.05.00